Low Grade Mathematics Practicum Digital Teaching Module to Improve Teaching Skills - Wiguna, Made Ceger Artha; Gede Wira Bayu; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2023)
The absence of digital teaching modules in lower-class mathematics courses has resulted in low student teaching skills. This research aims to produce a design to analyze the validity, practicality, and effectiveness of teaching modules on PGSD students' mathematics teaching skills. This research is research into the development of the ADDIE development model. The subject studied is a practical digital teaching module for mathematics learning. Meanwhile, the objects in the development stage are content validity, design, teaching module media, lecturer responses, and student responses. The data collection method used is a rating scale sheet. The data analysis technique used is qualitative analysis, which includes statements, input, and suggestions, and quantitative analysis, which includes descriptive analysis and inferential analysis, namely prerequisite tests and hypothesis tests using the t-test or one sample t-test. The research results show that the percentage of material experts, media experts, and design experts with overall validity qualifications is very high, and the percentage of practitioners is 87.95% with excellent qualifications. The effectiveness results show an influence of the use of digital teaching modules for lower-grade mathematics learning practicum on PGSD students' Mathematics teaching skills. It was concluded that the effective use of digital teaching modules for lower-grade mathematics learning practicums could improve PGSD students' Mathematics teaching skills.